PERAN ORANG TUA DALAM MENUNJANG PELAKSANAAN PEMBELAJARAN SOSIOLOGI DI SMAN 1 LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Krimanela, Resti; Basri, Wahidul; Erningsih, Erningsih (Pendidikan Sosiologi, 2013)
The background of this research was the parents role in supporting teaching sociology at SMAN 1 Linggo Sari Baganti. The purpose of this study describe the Role of Parents in Supporting Teaching Sociology at SMAN 1 Linggo Sari Baganti Pesisir Selatan District.The method used in this study is qualitative approach with descriptive type. Decision informants used by purposive sampling. This research informants are parents who have children that are still studying in high school education (high school) in SMAN 1 Linggo Sari Baganti and students of SMAN 1 Linggo Sari Baganti Pesisir Selatan District.The research findings known the role of parents in supporting the implementation of the sociology of learning at home are: 1) to meet the childs learning tool at home, parent is not maximized in the sense of the means provided inadequate. 2) In determining the childs learning or schedule an at home, parent is not optimal because they do not apply to her for making the rules and write schedule the home study. 3) In watching and guiding children in the home is not maximized their parents rarely pay attention and guide children learn at home. The reason parents busy and less assertive in determining a childs learning discipline and very easy to believe in his ability to learn . In accordance with the findings above it can be concluded that in supporting the learning of sociology at SMAN 1 Linggo Sari Baganti role of parents is not maximized.Based on the results of this study concluded the following: 1) a learning tool in meeting the child at home, parent is not maximized, 2) In determining the childs learning or schedule an at home, parent is not maximized, 3) In considering and guide children at home, parents not maximized